Coatings for concentrating solar systems – A review. (May 2015) - Atkinson, Carol; Sansom, Chris L.; Almond, Heather J.; Shaw, Chris P.
Abstract: Coatings are used extensively in concentrating solar systems to improve the performance of both reflectors and absorbers in terms of costs, efficiency, durability and maintenance. Different coatings are needed for different applications, operating conditions and material combinations as there are no universally perfect materials. There is also often wide variation in reported performance between nominally the same materials. The purpose of this review is to look at the underlying chemistry and stability of some of the main coatings that are in use or currently under investigation in order to identify reasons for the variations, gaps in knowledge and scope for performance improvement. It is evident that much better data on the intrinsic physical and chemical properties of the coatings and their performance are needed and would help avoid failures that may not be discovered for many years.